The choice - Roberts, Nora (New York : St. Martin's Press, 2022)
Breen Siobhan Kelly grew up in the world of Man and was once unaware of her true nature. Now she is in Talamh, trying to heal after a terrible battle and heartbreaking losses. Her grandfather, the dark god Odran, has been defeated in his attempt to rule over Talamh, and over Breen-for now. With the enemy cast out and the portal sealed, this is a time to rest and to prepare. Breen spreads her wings and realizes a power she's never experienced before. It's also a time for celebrations-of her first Christmas in both Talamh and Ireland, of solstice and weddings and births-and daring to find joy again in the wake of sorrow.
Keywords: Dragons -- Fiction; Good and evil -- Fiction; Heiresses -- Fiction; Magic -- Fiction; Imaginary places -- Fiction; Ireland -- Fiction; Fantasy fiction; Paranormal fiction; Romance fiction